Financial diaries as a research instrument to link cash flows with climate smart agriculture. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The project "Using Climate-Smart Financial Diaries for Scaling" in the Nyando Basin in Kenya provides unparalleled granular data on all transactions, cash and in-kind. Such high frequency data are key for understanding the potential smallholder demand for CSA financial products.